Treatment of metastatic squamous cell carcinoma arising in sacrococcygeal pilonidal sinus: a case report series - Ainara Soria Rivas; Sonia Bea-Ardebol; Elena Vida Navas; Óscar M. Muñoz-Arrones; Luis Jacobo Cabañas-Montero; Antonio Mena-Mateos; Fernando López-Campos; Sara Corral Moreno; Israel Pérez-Muñoz; Fausto González Lizan; María Sanz Pascual; Juan Jose Serrano Domingo (Frontiers in Medicine, 2023)
BackgroundSquamous cell carcinoma (SCC) arising in a sacrococcygeal pilonidal sinus is rare, with cases of metastatic disease being even rarer. Among published cases, almost none have reported on systemic treatment.ObjectiveThis disease has a poorer prognosis than other forms of cutaneous SCC; therefore, our objective is to shed some light on the treatment of metastatic disease.MethodsWe present a series of nine cases treated at a single center, four of whom received systemic treatment. Additionally, other previously reported cases of metastatic disease are included in an attempt to draw stronger conclusions.ResultsFour patients were treated under several treatment regimens, with a median progression-free survival of only 2 months and two instances of partial response (18%). The best result was achieved with cemiplimab. Across all the cases, there was a trend toward a benefit of the use of systemic treatment (HR 0.41, 95% CI 0.15–1.12, p = 0.083; median overall survival 13 vs. 8 months).LimitationsLimitations include the significant lack of information on previously published cases and the extremely heterogeneous nature of the existing information.ConclusionThe initial systemic treatment should be an anti-PD-1, as with other SCCs. After progression on anti-PD-1, there is no strong evidence to support the recommendation of a specific treatment or sequence: options include cetuximab and/or chemotherapy (platinum, paclitaxel, 5-fluorouracyl).